PENGARUH SISTEM PERPAJAKAN TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK - Fitria, Nur Laili; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze and to test of the tax systems as measured by the organizational structure, procedures, organization, organizational strategy and organizational culture on employee performance. While the sample of this study were employees who worked in the KPP Pratama Surabaya Krembangan totaling 40 employees. Data collection techniques in this study using a questionnaire. The data used in this research is the primary data collected by sending questionnaires to respondents. The research method in this research is quantitative, while the technique of analysis used in this study using multiple linear regression analysis. The results of the research value of the coefficient of determination of 69.3%, and each of the variables of organizational structure, organizational procedures, organizational strategy and organizational culture have positive influence on employee performance. While using the Feasibility Model all independent variables showed that the model fit for use for further research. Results of testing the hypothesis that the effect of the variable structure of the organization, procedure organization, organizational strategy and organizational culture have a significant effect on the performance of employees.Keywords: organization structure, organization procedure, organization strategy, organization culture, employeesâ Performance